Originary phenomenology, naïve and hypothetical - Gans, Eric Lawrence (2022)
I have lately taken to calling the basic operation of generative anthropology originary phenomenology, by way of insisting on the relative rigor of a procedure that formulates a hypothetical scenario of the first specifically human interactions as models to be applied to historical experiences of language, religion, and the arts, and potentially all forms of social and political organization.